Investigating the effects of smoothness of interfaces on stability of probing nano-scale thin films by Neutron Reflectometry - Jahromi, S.S.; Masoudi, S.F. (Condensed Matter Physics, 2012)
Most of the reflectometry methods which are used for determining the phase of complex reflection coefficient such as Reference Method and Variation of Surroundings medium are based on solving the Schrödinger equation using a discontinuous and step-like scattering optical potential. However, during the deposition process for making a real sample the two adjacent layers are mixed together and the interface would not be discontinuous and sharp. The smearing of adjacent layers at the interface (smoothness of interface), would affect the the reflectivity, phase of reflection coefficient and reconstruction of the scattering length density (SLD) of the sample. In this paper, we have investigated the stability of Reference Method in the presence of smooth interfaces. The smoothness of interfaces is considered by using a continuous function scattering potential. We have also proposed a method to achieve the most reliable output result while retrieving the SLD of the sample. Бiльшiсть методiв рефлектометрiї, що використовуються для визначення фази комплексного коефiцiєнту вiдбивання такi як еталонний метод i змiна прилеглого середовища грунтуються на розв’язку рiвняння Шредiнгера з використанням розривного i сходинкоподiбного оптичного потенцiалу розсiювання. Проте, пiд час процесу напорошування для пiдготовки реального зразка два сусiднi шари змiшуються i мiжфазова границя може не бути розривною i чiткою. Розмивання сусiднiх шарiв при мiжфазовiй границi (гладкiсть iнтерфейсу), може мати вплив на вiдбивання, фазу коефiцiєнта вiдбивання i перебудову густини довжини розсiювання зразка. В цiй статтi ми дослiдили стiйкiсть еталонного методу у присутностi гладких мiжфазових границь. Гладкiсть мiжфазових границь розглядається, використовуючи неперервну функцiю потенцiалу розсiювання. Ми також запропонували метод для отримання найбiльш надiйного результату, який вiдновлює густину довжини розсiювання зразка.